Arabic Reading Learning Techniques for Children based on Ali Achmad Madzkur’s Perspective - Asep Maulana (An-Nisa' Journal of Gender Studies, 2022)
Arabic is one of the official languages of the United Nations, which is essential for all nations to have as a means of global communication between countries. In a country with a majority Muslim population like Indonesia, apart from being a means of communication, Arabic has a special place as a medium for worship and deepening knowledge of the Islamic religion. Mastering Arabic is necessary for all Muslims, young and old, even children. Non-Arabic speakers cannot automatically master Arabic because it is not their mother tongue; therefore, specific techniques to learn it, especially in reading skills. This study aims to describe comprehensively the technique of learning to read Arabic from the perspective of Ali Achmad Madzkur. The researcher uses a qualitative approach with descriptive methods in this type of literature research. The study results stated that the techniques of learning to read Arabic for children from the perspective of Ali Achmad Madzkur include; listening and speaking techniques, reading aloud techniques, analysis techniques, letter identification techniques, and composing techniques.